Occupational Gender Stereotypes in Indonesian Secondary School English Language Textbooks - Sella Rohmawati; Kristian Adi Putra (Universitas Hamzanwadi, 2022)
This discourse study seeks to examine occupational gender stereotypes in two textbooks of secondary English language textbooks published in Indonesia. Occupational gender stereotypes in two English textbooks, entitled When English Rings a Bell, for grade 7 and 8 were analyzed with the help of Kress and van Leeuwen (2006) framework. The findings indicate that both textbooks encompass content on gender stereotypes, particularly occupation. The findings also revealed that there were far less photos of women in the public domain than there were of men, indicating that women in conventional gender roles such as cooking, cleaning, watering plants, caring for children, and performing all domestic activities were far more common. Furthermore, the study found that male occupations were more common and diverse than female occupations in terms of occupational gender stereotypes. Furthermore, in terms of societal responsibilities, males were demonstrated to have a wider choice of vocations than girls. Gender blindness among curriculum designers and textbook authors is a serious worry in this regard, and it must be addressed in order to improve awareness of gender-related occupations. The study's practical implications are that English teachers, language textbook authors, curriculum creators and illustrators should be fully aware of the interplay between language, visual depictions, and gender concerns while constructing language textbooks to avoid unwanted insights into occupational gender stereotypes.